Gastrointestinal side effects of Chemotherapy: Parent s’ Perception towards Children with Cancer - Hamzah AL-Shujairi, Nariman (Journal of Neonatal Surgery, 2025)
Background: Children before the age of 18 years are highly vulnerable to certain life-threatening diseases such as cancer, which is predicted from statistical evidence in the literature reviewed and in need of chemotherapy medications with side effects. Objectives: This study aimed to assess parents’ perception of children with cancer complaining of gastrointestinal side effects of chemotherapy. Materials and Methods: A cross-sectional study was conducted during the period (from October 4, 2023, to January 26, 2024) at Al-Furat Al-Awsat Oncology Hospital in Al-Najaf Al-Ashraf City using a questionnaire structured for objective achievement. The questionnaire consisted of a demographic and clinical data section and the parents’ perception of the gastrointestinal side effects of chemotherapy. Statistical and inferential analyses were performed to examine the data. Data were collected from (113) participants who selected nonprobability (convenience) by the interview researcher. Results: The study specified that mothers comprised the majority of the sample and their ages were between (41 and 50), while the sickest children were male and female. Loss of appetite and taste changes were the most effective gastrointestinal side effects of chemotherapy, and the overall perception of the parents was good. Conclusions: This study demonstrated that most patients suffer from loss of appetite and taste change, and they have a good perception of this side effect. This result emphasizes the importance of providing sufficient information to parents about any side effects that could appear in a child after a chemotherapy session.